Museografia - Minissi, Franco; Ranellucci, Sandro (Roma : Bonsignor, 1992)
Convenio con la Universidad de "La Sapienza", Roma.
Keywords: MUSEOGRAFIA; PATRIMONIO ARQUITECTONICO; RELEVAMIENTOS; MUSEOS; RESTAURACION; REFUNCIONALIZACION ARQUITECTONICA; RECONSTRUCCION; PRESERVACION ARQUITECTONICA